2019
DOI: 10.2196/12135
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone App for the Self-Management of Pediatric Concussion: Development and Usability Testing

Abstract: Background Concussion is a common injury among Canadian children and adolescents that leads to a range of neurobehavioral deficits. However, noticeable gaps continue to exist in the management of pediatric concussion, with poor health outcomes associated with the inadequate application of best practice guidelines. Objective The aim of this study was to describe the development and assess the usability of a mobile phone app to aid youth in the self-management of concussi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The participants' group P, C and S mentioned the screening exam reminder, sharing button and prompt, and it is perceived as cues to action. In accordance with the present results, previous studies have demonstrated that the reminder system is an effective and acceptable intervention (Brown and Rahman, 2018;Heo et al, 2013;Sandhu et al, 2019). Meanwhile, a sharing button matches those observed in earlier studies for resource sharing, social engagement, providing support and promotion to others (Anderson et al, 2016;Baumel and Muench, 2016;Lapointe et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The participants' group P, C and S mentioned the screening exam reminder, sharing button and prompt, and it is perceived as cues to action. In accordance with the present results, previous studies have demonstrated that the reminder system is an effective and acceptable intervention (Brown and Rahman, 2018;Heo et al, 2013;Sandhu et al, 2019). Meanwhile, a sharing button matches those observed in earlier studies for resource sharing, social engagement, providing support and promotion to others (Anderson et al, 2016;Baumel and Muench, 2016;Lapointe et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Although there were limited search results specific to paediatric overweight and obesity, the broader search identified further methods of testing usability and engagement of mHealth interventions for other paediatric health conditions including concussion [53] and mild traumatic brain injury [54]. The most extensively used measure of usability function is task success; it is highly probable that issues exist with a digital tool if the user is unable to complete a given task [46].…”
Section: Comparison With Usability and Engagement Testing In Other Ar...mentioning
confidence: 99%
“…One method of measuring efficiency or the level of effort that users provide to achieve tasks is by assessing task completion time, including error and correction time [46]. Tasks completed in less time indicate that less effort was required to complete them, which is believed to enhance the overall experience [53]. However, the length of time required will depend on the nature of the task which means time comparisons and efficiency can only be evaluated if the same task is performed [55].…”
Section: Comparison With Usability and Engagement Testing In Other Ar...mentioning
confidence: 99%
See 1 more Smart Citation
“…This involvement is a way of ensuring the validity of the content of the mobile app [ 15 ] and that it meets the users’ needs and requirements [ 16 ], increasing its likelihood of being usable. Usability is an essential criterion in the evaluation of mHealth apps [ 17 , 18 ] and has been defined as the extent to which a product can be used by users to achieve specific goals with effectiveness, efficiency, and satisfaction and in a specific context of use [ 19 ]. Nevertheless, a systematic review that synthesized and evaluated existing studies on the assessment of the usability of pain-related apps found 31 manuscripts on the usability of 32 pain apps [ 20 ].…”
Section: Introductionmentioning
confidence: 99%